2020
DOI: 10.26740/bisma.v12n2.p154-167
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and strategy for improving Indonesian coffee competitiveness in the international market

Abstract: In order to face a competitive market environment, knowing the position of the product itself and competitors is needed. Coffee is the main tropical commodity traded in the world. Coffee has great potential and is very competitive. The research objective is to determine the competitiveness of Indonesian coffee and processed coffee beans exports in the international market by using Revealed Comparative Advantage (RCA) to analyze the trade that occurs in several other major exporters such as Brazil, Colombia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
1
10
0
5
Order By: Relevance
“…Kopi merupakan komoditas tropis utama yang diperdagangkan di dunia, dengan kontribusi setengah dari total ekspor komoditas tropis lainnya. Kopi ialah salah satu jenis minuman yang disukai oleh sebagian besar gaya hidup masyarakat Indonesia khususnya di kota Surabaya (Rahardjo et al, 2020). Masyarakat Indonesia cenderung menghabiskan waktu luangnya di kafe favorit.…”
Section: Pendahuluanunclassified
“…Kopi merupakan komoditas tropis utama yang diperdagangkan di dunia, dengan kontribusi setengah dari total ekspor komoditas tropis lainnya. Kopi ialah salah satu jenis minuman yang disukai oleh sebagian besar gaya hidup masyarakat Indonesia khususnya di kota Surabaya (Rahardjo et al, 2020). Masyarakat Indonesia cenderung menghabiskan waktu luangnya di kafe favorit.…”
Section: Pendahuluanunclassified
“…Juhász, 2013;Török and Jámbor, 2013;Shalbuzov, 2020). Rahardjo et al (2020) tried to investigate the competitiveness of Indonesian coffee in the international market by using Revealed Comparative Advantage (RCA) index and Export Product Dynamics (EPD). Results indicated that low value of RCA implying the comparative advantage of Indonesia still needs to be improved because of losing opportunities to be able to trade with other countries.…”
Section: Export Competitiveness Of Tea and Other Agricultural Productsmentioning
confidence: 99%
“…Sebaliknya, nilai RCA yang lebih kecil dari satu menunjukkan bahwa daya saing produk tergolong lemah (Mudjayani, 2008dalam Haryotejo, 2013. RCA dihitung dengan persamaan (Rahardjo et al, 2020) 𝑅𝐶𝐴 dengan 𝑋 𝑜,𝑖 adalah nilai ekspor POKI ke negara i, 𝑋 𝑇𝐸,𝑖 adalah total ekspor seluruh komoditas Indonesia ke negara i, 𝑋 𝑜𝑤,𝑖 adalah nilai ekspor produk olahan kopi dunia ke negara i, dan 𝑋 𝑇𝐸𝑤,𝑖 adalah total nilai ekspor seluruh komoditas dunia ke negara i.…”
Section: Revealed Comparative Advantage)unclassified